Th1 bias of liver mucosal‐associated invariant T cells promotes hepatic gluconeogenesis in type 2 diabetes mellitus - Tang, Wenjuan; Ge, Kang; Shen, Lei; Wang, Hongdong; Feng, Wenhuan; Sun, Xitai; Chu, Xuehui; Zhu, Dalong; Yin, Hongli; Bi, Yan (Diabetes/metabolism research and reviews, 2023)
Aims It is acknowledged that aberrant liver immunity contributes to the development of type 2 diabetes mellitus (T2DM). Mucosal‐associated invariant T (MAIT) cells, an innate‐like T‐cell subset, are enriched in the human liver. Nevertheless, the characterisation and potential role of hepatic MAIT cells in T2DM remain unclear. Materials and methods Fourteen newly diagnosed T2DM subjects and 15 controls received liver biopsy. The frequency and cytokine production of MAIT cells were analysed by flow cytometry. The expression of genes involved in glucose metabolism was determined in HepG2 cells co‐cultured with hepatic MAIT cells. Results Compared with controls, hepatic MAIT cell frequency was significantly increased in T2DM patients (24.66% vs. 14.61%, p = 0.001). There were more MAIT cells producing interferon‐γ (IFN‐γ, 60.49% vs. 33.33%, p = 0.021) and tumour necrosis factor‐α (TNF‐α, 46.84% vs. 5.91%, p = 0.021) in T2DM than in controls, whereas their production of interleukin 17 (IL‐17) was comparable (15.25% vs. 4.55%, p = 0.054). Notably, an IFN‐γ+TNF‐α+IL‐17+/−producing MAIT cell subset was focussed, which showed an elevated proportion in T2DM (42.66% vs. 5.85%, p = 0.021) and positively correlated with plasma glucose levels. A co‐culture experiment further indicated that hepatic MAIT cells from T2DM upregulated the gene expression of pyruvate carboxylase, a key molecule involved in gluconeogenesis, in HepG2 cells, and this response was blocked with neutralising antibodies against IFN‐γ and TNF‐α. Conclusions Our data implicate an increased Th1‐like MAIT cell subset in the liver of newly diagnosed T2DM subjects, which induces hyperglycaemia by promoting hepatic gluconeogenesis. It provides novel insights into the immune regulation of metabolic homoeostasis. Clinical trial registration number NCT03296605 (registered at www.clinicaltrials.gov on 12 October 2018).